The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1029/2021gh000529
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Air Pollutants and Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Time Stratified Case‐Crossover Design With a Distributed Lag Nonlinear Model

Abstract: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is an important clinical event characterized by an aggravation of the patient's respiratory symptoms whose degree exceeds the range of daily variation, leading to changes in the drug treatment regimen; it is the main cause of death from chronic obstructive pulmonary disease (COPD) on a global scale (Shen & Wang, 2020). The Global Burden of Disease study pointed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…This suggests that the immediate effects of these air pollutants were stronger than the delayed effects. Furthermore, low levels of SO 2 and CO exhibited a protective effect on AECOPD, which gradually increased over time until a lag of 27 days (39). The nonlinear effects of different air pollutants on AECOPD varied based on factors such as gender, age, and seasons (40).…”
Section: Figurementioning
confidence: 98%
“…This suggests that the immediate effects of these air pollutants were stronger than the delayed effects. Furthermore, low levels of SO 2 and CO exhibited a protective effect on AECOPD, which gradually increased over time until a lag of 27 days (39). The nonlinear effects of different air pollutants on AECOPD varied based on factors such as gender, age, and seasons (40).…”
Section: Figurementioning
confidence: 98%
“…The worldwide COVID-19 pandemic burden had reached approximately 63 billion cases as of November 2022, with massive breakouts in different countries [ 1 ]. Chronic obstructed pulmonary disease (COPD) affected over 251 million people worldwide, and 3.17 million deaths were reported each year [ 2 , 3 ]. According to the World Health Organization (WHO) report 2022, based on electronic data collected from 215 countries, approximately 40 million people were treated for multidrug and rifampicin-resistant tuberculosis (MDR/RR-TB) worldwide, with 649,000 adults and 17,700 children receiving treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2020 Report on the State of Ecology and Environment in China issued by Ministry of Ecology and Environment showed that 43.3% of 337 cities exceeded the ambient air quality standard (2020). As people pay more attention to environmental pollution, some studies on the association between COPD and air pollution have been conducted in China (Feng et al 2019 ; Jin et al 2022 ; Lin et al 2020 ; Liu et al 2022 ; Qiu et al 2018 ; Zhang et al 2020 ; Zhang et al 2018 ). However, these studies found different components of air pollutants affecting COPD admissions, with inconsistent conclusions and lack of research analysis in recent years.…”
Section: Introductionmentioning
confidence: 99%